Compare the effect of high and low doses of atorvastatin on the levels of high-sensitivity C-reactive protein in patients with acute coronary syndrome - Zamani, Bijan; Babapour, Behzad; Doustkami, Hosein; Mousavi, Mirhashem (International Journal of Research in Medical Sciences, 2016)
Background: Findings of other researches indicate that inflammation process is one of the most important molecular interactions mediated in atherosclerosis and the inflammation indexes of plasma level such as high-sensitivity C-reactive protein (hs-CRP) is regarded to predict the risk of cardio-vascular diseases. According to various studies, statins are certainly effective in the prevention of atherosclerosis and anti-inflammatory role of atorvastatin by lowering effect on hs-CRP can be considered. The aim of this study was to compare the effect of high and low doses of atorvastatin on levels of hs-CRP in patients with acute coronary syndrome. Methods: This is a clinical trial study that has been done on 180 patients with acute coronary syndrome who referred to Imam Khomeini hospital in Ardabil. Patients were divided in 2 groups randomly. Atorvastatin with low dose (20mg) and high dose (40mg) with routine treatments were given to first and second groups, respectively. The hs-CRP level was evaluated for all patients in hospitalized time and third month late. Data were collected and analyzed by statistical methods in SPSS.19. Results: Of all patients, 40 patients (22.2%) was assayed with STEMI, 8 patients (4.4%) with N/Q WMI and132 patients (73.3%) with U/A. 125 patients (69.4%) were male and rest of them were female. The age average of patients was 59.1±8.1 years. 74 (41.1%) of patients had blood pressure and 35 (19.4%) use smoke. After three months, in group with low dose, 81 patients (90%) and in group with high dose 85 patients (94.4%) improved. The atorvastatin with high dose could significantly decrease the hs-CRP ratio with 40% more than other group with 13.3%. Conclusions: In this study high dosage of atorvastatin could lessen significantly the hs-CRP and LDL ratio compared to atorvastatin with low dosage.